Defective HDL particle uptake in ob/ob hepatocytes causes decreased recycling, degradation, and selective lipid uptake - Silver, David L. (American Society for Clinical Investigation, 2000)
Levels of plasma HDL are determined in part by catabolism in the liver. However, it is unclear how the hepatic catabolism of holo-HDL is regulated or mediated. Recently, we found that ob/ob mice have defective liver catabolism of HDL apoproteins in vivo that can be reversed by low-dose leptin treatment. Here we examined HDL catabolism and trafficking at the cellular level using isolated hepatocytes. We demonstrate that ob/ob hepatocytes have reduced binding, association, degradation, and resecretion of HDL apoproteins and 50% less selective lipid uptake relative to wild-type hepatocytes. In addition, HDL apoproteins were found to colocalize with transferrin in the general endosomal recycling compartment (ERC) in wild-type hepatocytes. However, the localization to the ERC was markedly reduced in ob/ob hepatocytes. Filipin staining of cellular cholesterol revealed decreased cholesterol in the ERC in ob/ob hepatocytes. Defects in HDL cell association and cholesterol distribution were reversed by leptin administration. The findings show a major defect in HDL uptake and recycling in ob/ob hepatocytes and suggest that HDL recycling through the ERC plays a role in the determination of plasma HDL protein and cholesterol levels.